Financial Costs of Emergency Department Presentations for Australian Patients With Heart Disease in the Last 3 Years of Life - Sanjeewa Kularatna; Jessie Wong; Sameera Senanayake; David Brain; Jaimi Greenslade; William Parsonage; Deokhoon Jun; Steven McPhail (SAGE Publishing, 2022)
Aims: This study described emergency department (ED) resource use patterns and associated costs among patients with heart disease in their last 3 years of life in a high-income country. Methods: This study used linked data from ED and death registry databases in Australia. A random sample of 1000 patients who died due to any cause in 2017, and who had been living with heart disease for at least the prior 10-years were included. The outcomes of interest were number of ED presentations over each of the last 3 years prior to death and relative cost contributions of ED-related items. Results: The number of patients needing ED care and number of ED presentations per patient increased as patients were closer to death, with 85% experiencing at least one ED presentation in their last year of life. Mean per patient ED presentation cost increased with each year closer to death. Costs related to labor, pathology, patient travel, and goods and services contributed more than 85% of the total cost in each of the 3 years. Conclusion: The increase in cost burden as patients neared death was attributable to more frequent ED presentations per person rather than more expensive ED presentations. The scope of this study was limited to ED presentations, and may not be representative of heart-disease-related end-of-life care more broadly.